Identification of causative agent for fungal infection and effect of disinfectants on hatching and survival rate of common carp (C. carpio) larvae (Asian Journal of Medical and Biological Research, 2016)
Common carp (Cyprinus carpio) is one of the commercially important and commonly cultured fish. In the hatchery intensive incubation leads to microbial overgrowth in C. carpio eggs that hamper egg development, hatchability and larval survivability. The aim of this study is to find out causes of mass mortality in C. carpio eggs during peak- breeding season between March to May 2015 at Mafatema fish hatchery, Chanchra, Jessore sadar upazilla. In the present study three disinfectants with three different concentrations in each such as methylene blue 1, 3 and 5mg/L., malachite green 1, 3 and 5mg/L., sodium chloride 1, 2 and 3g/L were used to observe the hatching rate of fertilized eggs and survival rate of larvae. Bacterial load of culture water was examined during the induced breeding of C. carpio with mycological examination of egg samples with different disinfectants. The total bacterial count fluctuated from 3.4 x 108 CFU/ml to 32.7 x 108 CFU/ml during the period of fertilization to 4days of hatching. The fertilized eggs infected by Saprolegnia spp. were appeared as tuft hairy like balls with a white cottony envelop. Among all the treatment 1mg/L methylene blue, 3mg/L malachite green and 1g/L sodium chloride showed significantly better (P